Potret Keselarasan Agama, Budaya dan Lingkungan Masyarakat Silurah: Nyadran Gunung - Afad, Mochammad Najmul (Balai Pelestarian Kebudayaan Wilayah X, 2022)
This paper attempts to present the ethnography of Nyadran Gunung which is a tradition of Silurah community. This research uses ethnographic approach to obtain in-depth data on the knowledge and experience of Silurah community about Nyadran Gunung. The results of this study shows that the tradition of Nyadran Gunung is the cultural behavior of community that has been inherited from generation to generation. This ritual is performed by the entire Silurah community, young, old, children, men and women. Nyadran Gunung is a religious rite which is also a process of harmony between religion, nature, society and culture. Nyadran Gunung is a ritual that brings together aspects of environmental balance (cosmos), religion and culture of Silurah Community. This ritual portrays the involvement of the community with all elements in preserving nature and community culture. Nyadran Gunung answered the importance of protecting nature in the midst of environmental damage.